Hemiballism with leg predominance caused by contralateral subthalamic haemorrhage. (9th April 2015) - Noda, Kazuyuki; Hattori, Nobutaka; Okuma, Yasuyuki
Abstract : Hemiballism is a rare movement disorder characterised by high-amplitude movements of the limbs on one side of the body. Stroke of the contralateral basal ganglia, especially the subthalamic nucleus (STN) is the most common aetiology of acute development of hemiballism. Recently, the pathophysiology of hemiballism has been associated with abnormal firing patterns in the globus pallidus interna, with intermittent firing bursts followed by pauses, during which movements occur. An 87-year-old woman presented with a 5-day history of hemiballism predominantly in her leg. On the basis of her brain MRI findings, she was diagnosed as having vascular hemiballism caused by haemorrhage in the contralateral STN. Treatment with risperidone led to the clinical resolution of her condition. We discuss the distribution of the patient's ballistic movements on the basis of the somatotopic organisation of the STN.